Sensasi Gurat Alam dalam Fotografi Seni - Muh. Fajar Apriyanto (Rekam: Jurnal Fotografi, Televisi, Animasi)
Nowadays art expressions know no media boundaries, whatever the toolsand materials, an artist can use the media in order to express his artistic ideas. Photography does not have mere documentary functions, but also serves as an expression of feelings or aesthetic emotions through artistic elements such as lines, colors, texture, tone, compositions, and balance.This photography art creation entitled The Sensation of Natural Scratchesin Art Photographic is an emotional expression that is based on the aesthetic experiences of the details on old teak wood. The photography objects were decayed teak that were once used to build houses and has been worn by continuous changes of weather from hot sun to cold hard winds which created scratches on the teak’s texture. The focus is on the teak’s texture’s detail or on certain patterns which can express the emotions artistically and is presented with the creative-aesthetic approach. The aesthetic experiences were gained from the hobby of collecting the old teaks. The art creation was focused on the creative-aesthetic approach and the interpretation of values in the details of the worn out teak. Additionally, it is emphasized on the compositions and the photography techniques such as the choice of objects, the use of the perfect lighting, the use of picture formatting, and the viewpoint processing. Through these approaches the photos are hoped to show aesthetic sensations which are comes from the result of scratches and textures that appeared in worn out teak. On the other hand, some other considerations of photography techniques are held in order to gain new values and interpretations. The interpretation process and the comprehension of the values have been the main focus; or in a much specific sense, photography is more valuable in the acceptance and its value is determined by the viewers and researchers, and not on the photographer. Therefore these photos may offer new experiences in interpreting the details on worn out teak. Hence, as a whole, old and worn out teak, in the photographic sense, has its own aesthetic value as an object of photography, it can also enrich the perception of visual experiences for its viewers.